Global antibiotic consumption 2000 to 2010: an analysis of national pharmaceutical sales data - Van Boeckel, Thomas P; Gandra, Sumanth; Ashok, Ashvin; Caudron, Quentin; Grenfell, Bryan T; Levin, Simon A; Laxminarayan, Ramanan (The Lancet infectious diseases, 2014)
Antibiotic drug consumption is a major driver of antibiotic resistance. Variations in antibiotic resistance across countries are attributable, in part, to different volumes and patterns for antibiotic consumption. We aimed to assess variations in consumption to assist monitoring of the rise of resistance and development of rational-use policies and to provide a baseline for future assessment. With use of sales data for retail and hospital pharmacies from the IMS Health MIDAS database, we reviewed trends for consumption of standard units of antibiotics between 2000 and 2010 for 71 countries. We used compound annual growth rates to assess temporal differences in consumption for each country and Fourier series and regression methods to assess seasonal differences in consumption in 63 of the countries. Between 2000 and 2010, consumption of antibiotic drugs increased by 35% (from 52 057 163 835 standard units to 70 440 786 553). Brazil, Russia, India, China, and South Africa accounted for 76% of this increase. In most countries, antibiotic consumption varied significantly with season. There was increased consumption of carbapenems (45%) and polymixins (13%), two last-resort classes of antibiotic drugs. The rise of antibiotic consumption and the increase in use of last-resort antibiotic drugs raises serious concerns for public health. Appropriate use of antibiotics in developing countries should be encouraged. However, to prevent a striking rise in resistance in low-income and middle-income countries with large populations and to preserve antibiotic efficacy worldwide, programmes that promote rational use through coordinated efforts by the international community should be a priority. US Department of Homeland Security, Bill & Melinda Gates Foundation, US National Institutes of Health, Princeton Grand Challenges Program.